2008
DOI: 10.1038/sj.bjc.6604715
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of HLA Class I molecules in the tumour is associated with a poor prognosis in patients with oesophageal squamous cell carcinoma

Abstract: As antigenic peptides in the context of human leukocyte antigen (HLA) class I molecules are recognised by cytotoxic T lymphocytes (CTL), the downregulation of HLA class I molecules is one of the reasons why tumour cells can evade CTL-mediated anti-tumour immunity. In this study, we investigated HLA class I expression in oesophageal squamous cell carcinoma (ESCC) (n ¼ 70) and in their metastatic lesions (lymph nodes (n ¼ 40) and liver (n ¼ 3)), by immunohistochemistry with anti-HLA class I monoclonal antibody (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
65
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 29 publications
13
65
2
2
Order By: Relevance
“…Relapse-free survival increased significantly in the MHC class I-positive patients compared to the negative patients in the total patient group and the chemotherapy-only group, but not in the PSK group. PSK, protein-bound polysaccharide K. prognosis have been reported to be correlated in various types of cancer, including breast, lung, renal cell carcinoma and colon cancer (8,9,(17)(18)(19). The present study found that the expression rate of MHC class I in primary gastric cancer lesions was 55%, close to the values that have been reported in other studies (20).…”
Section: Correlation Between Expression Of Mhc Class I and Efficacy Osupporting
confidence: 86%
“…Relapse-free survival increased significantly in the MHC class I-positive patients compared to the negative patients in the total patient group and the chemotherapy-only group, but not in the PSK group. PSK, protein-bound polysaccharide K. prognosis have been reported to be correlated in various types of cancer, including breast, lung, renal cell carcinoma and colon cancer (8,9,(17)(18)(19). The present study found that the expression rate of MHC class I in primary gastric cancer lesions was 55%, close to the values that have been reported in other studies (20).…”
Section: Correlation Between Expression Of Mhc Class I and Efficacy Osupporting
confidence: 86%
“…In both murine models and human studies, the expression of CIITA, MHCI, and/or MHCII molecules can influence antitumor immune responses (41)(42)(43). Consistent with this, the expression of MHCI and/or MHCII molecules on tumor cells has been repeatedly shown to impact prognosis (44)(45)(46). Thus, our data raise the possibility that in addition to targeting the mitogenic and survival signals emanating from the EGFR, EGFRIs may influence the immune response to tumor cells by altering the expression of MHCI and/or MHCII molecules.…”
Section: Discussionmentioning
confidence: 72%
“…However, the frequency of this downregulation varies significantly between tumor types. It can be as high as 48% in esophageal cancer but only 29% in ovarian cancer (34,35). These findings suggest that MHC downregulation is not the only cause of immune escape by tumors.…”
Section: Mhc Downregulation and The Loss Of Immunogenicitymentioning
confidence: 95%